Nutritional and dietary requirements of the elderly with chronic kidney disease in ambulatory hemodialysis - Almeida Pacasi, Katherine Lizbeth (2021)
Chronic kidney disease is a progressive disease that affects the glomeruli. The objective of this research was to establish the nutritional and dietary requirements of the elderly with chronic kidney disease on ambulatory hemodialysis. The study was descriptive level of secondary sources and the population was older adults with hemodialysis. The study subject requires 1.1 to 1.2 g / kg protein weight to cover the protein turnover rate and losses during hemodialysis; likewise, sodium, potassium and phosphorus requirements are reduced; as for the others, macro and micronutrients sufficient according to the adequacy for the elderly. The following conclusion was reached: The nutritional requirement is modified by increasing the intake of protein and energy, reducing and controlling food sources of sodium, potassium, phosphorus and water.